Analisis Strategi Pemasaran Produk Makcan Food di Masa Pandemi Covid-19 - Pangestu, Adinda Rizky Hayu (Jurnal Mahasiswa Manajemen, 2022)
During the Covid pandemic, not all MSMEs in the trade sector suffered a rise in demand. However, there are still problems that arise such as difficulty in obtaining raw materials, weather conditions and significant price increases, that can be posing a threat to the production and distribution process. So, many have swerved to replace the product with another product. The aim of this study was to analyze the marketing strategy of MSMEs products in Gresik during the pandemic, especially Makcan Food products. This type of research is a qualitative research with a literature study approach. The type of data used is primary data with data retrieval conducted through online interviews with WhatsApp voice notes and directly. The results of this study prove that not all businesses built after COVID-19 have experienced difficulties and declines. Business owners must also be able to pick up balls that can be used as opportunities to continue to innovate and be creative, as well as the right use of social media to attract consumer interest. This research can be considered in determining the right marketing strategy to increase sales of Makcan Food products. This research is limited to Makcan Food, to find out more about the impact of Covid-19 on a business. Might be able to do research in other objects and areas